2018
DOI: 10.1016/j.injury.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation and non-selectivity of Dakin’s solution prevents effectiveness in contaminated musculoskeletal wound models

Abstract: We did not observe evidence of a therapeutic benefit following Dakin's solution treatment for any tested concentration or application method in two contaminated musculoskeletal wound models. Despite confirmation of robust bactericidal activity in vitro, our findings suggest DS at current clinically-used concentrations does not kill tissue surface-attached bacteria, nor does it necessarily cause host tissue toxicity that exacerbates infection in the setting of complex musculoskeletal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Both H 2 O 2 and HOCl are produced by neutrophils to break down pathogenic and foreign substances and have been used to treat wound infections (Wang et al 2007). Dilute sodium hypochlorite (Dakin's solution) has also been used for wound debridement (Degnim et al 2013;Mangum et al 2018). We previously investigated infections postbreast and axillary operations and found that including Dakin's solution in postoperative care reduced bacterial colonization of drainage tubes (Degnim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Both H 2 O 2 and HOCl are produced by neutrophils to break down pathogenic and foreign substances and have been used to treat wound infections (Wang et al 2007). Dilute sodium hypochlorite (Dakin's solution) has also been used for wound debridement (Degnim et al 2013;Mangum et al 2018). We previously investigated infections postbreast and axillary operations and found that including Dakin's solution in postoperative care reduced bacterial colonization of drainage tubes (Degnim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Introduced more than 100 years ago, NaOCl solutions remain a standard of care in the disinfection of external soft tissue wounds [54]. Irrigants containing one or multiple antibiotics have also been discussed, as they selectively kill the invading microorganisms and obviously cause less collateral damage than non-specific biocides such as NaOCl [55]. There is also a history of glutaraldehyde usage in antiseptic solutions [56] and despite the fact that it is still contained in some dentine bonding agents [57], the high toxicity and mutagenic potential of this chemical would preclude it from the application proposed by Waly (1995) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Our institution utilised a 0.125% (quarter‐strength) Dakin's solution in accordance with this principle. It should be noted, however, that recent studies have suggested that Dakin's cytotoxic effects may remain at much lower concentrations, although this is an area of on‐going research …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that recent studies have suggested that Dakin's cytotoxic effects may remain at much lower concentrations, although this is an area of on-going research. [32][33][34] In our study, Dakin's and Prontosan were utilised as the initial or only instillation solutions in all the cases. Early in our series, Prontosan was used exclusively when we were presented with an open wound with exposed hardware due to institutional policy regarding Dakin's solution instillation.…”
Section: Discussionmentioning
confidence: 99%